Study on sealing performance of packer rubber based on stress relaxation experiment. (November 2021) - Zheng, Xu; Li, Bin
Highlights: The laser strain sensor was used to obtain accurate experimental data. The actual working temperature and relaxation have profound effects on sealing performance of rubber. The main failure mechanism caused by temperature and relaxation have been discussed. Temperature safety factor and stress relaxation safety factor were put forward. Abstract: In the last few decades, rubber seal elements have been extensively used in the oil and gas industry. However, mechanical properties of rubber decrease at high temperatures, and stress relaxation can lead to sealing performance degradation, even sealing element failure. Therefore, how high temperature and stress relaxation affect the sealing performance of rubber is an important issue in oil and gas production. According to the oilfield feedback information, hydrogenated nitrile butadiene rubber (HNBR) was chosen for sample tension test at different temperature (20 °C and 120 °C) and the stress relaxation tests at 120 °C. The constitutive model of rubber was fitted by the test data. At the setting pressure of 14 MPa, the influence of temperature and stress relaxation on the packer rubber seal system was investigated by finite element analysis (FEA) software. The results indicated that temperature and stress relaxation had an appreciable impact on the sealing performance of packer rubber seal system. The average contact stress at 120 °C between the rubber and the borehole wall, compared with the calculation results at 20 °C, decreased by more than 15% and the maximum contact stress decreased by 20%. Similarly, the average contact stress before the relaxation decreased by more than 35% after stress relaxation behavior at 120 °C. In addition, the maximum contact stress decreased by 50% due to the stress relaxation. Our experimental results and discussion enable us to provide some advice to improve the sealing performance of a packer seal system, and present a basic experimental and theoretical foundation for future research into the optimum design of a packer sealing system.